Управління ризиками банківської діяльності в контексті сучасних тенденцій її трансформації - Грабчук, Оксана Миколаївна; Hrabchuk, Oksana; Фатєєва, Тетяна Сергіївна; Fatieieva, Tatiana (Дніпровський державний аграрно-економічний університет, 2023)
Стаття присвячена визначенню напрямів удосконалення управління ризиками банківської діяльності в контексті сучасних тенденцій трансформації банківського бізнесу. Визначено сучасні тенденції трансформації банківського бізнесу, пов’язані із зміною суспільних інститутів та впровадженням технологічних інновацій. Охарактеризовано контекстні зміни змісту основних форм банківських ризиків (кредитного, ринкового, операційного, репутаційного, легального, регуляторного). Проаналізовано переваги та недоліки методів оцінки банківських ризиків та запропоновано послідовність формування внутрішньобанківської системи оцінювання ризиків, яка дасть змогу адаптуватись банку до сучасних тенденцій трансформації банківського бізнесу. У процес формування внутрішньобанківської системи оцінювання ризиків запропоновано включити формування внутрішньобанківської класифікації ризиків; розробку процедур їх систематичного моніторингу; формування систем комунікації та звітності щодо оцінки ризиків; формування внутрішньої системи контролю ризиків; автоматизацію процесів оцінки та контролю ризиків; удосконалення методичного забезпечення та підвищення професійної кваліфікації співробітників; взаємодію з регуляторами; оцінку зовнішніх умов та кризових впливів. Визначено відповідні напрями перетворення системи управління банківськими ризиками за її основними компонентами. The article is devoted to the determination of directions for improvement of banking risk management in the context of modern trends in the transformation of banking business. The following methods were used in this research: structural decomposition (analysis of the components of the banking risk management system), analysis (identification of modern trends in the transformation of banking business, analysis of the advantages and disadvantages of banking risk assessment methods), synthesis (development of the sequence of formation of an intrabank risk assessment system, determination of directions for improvement of the components banking risk management systems). Modern trends in the transformation of the banking business associated with changes in social institutions and the introduction of technological innovations have been identified. The contextual changes in the content of the main forms of banking risks (credit, market, operational, reputational, legal, regulatory) are characterized. The advantages and disadvantages of banking risk assessment methods are analyzed and the sequence of formation of an intrabank risk assessment system is proposed, which will give the bank an opportunity to adapt to modern trends of the transformation of banking business. In the process of formation of an intrabank risk assessment system, it is proposed to include the formation of an intrabank risk classification; development of procedures for their systematic monitoring; formation of communication and reporting systems for risk assessment; formation of an internal risk control system; automation of risk assessment and control processes; improvement of methodological support and improvement of professional qualifications of employees; interaction with regulators; assessment of external conditions and crisis influences. The corresponding directions of the transformation of the banking risk management system according to its main components have been determined: development and individualization of the risk management policy; ensuring compliance of the risk management policy with regulatory requirements; development and implementation of internal risk management procedures; innovativeness of banking business technologies; development of business continuity.
Risk management of banking activities in the context of current trends of its transformation
Keywords: ризики банківської діяльності; banking activity risks; трансформація банківського бізнесу; banking business transformation; ідентифікація ризиків; risk identification; оцінювання ризиків; risk assessment; система управління ризиками; risk management system; стратегія розвитку банку; bank development strategy